Relict Species: Phylogeography and Conservation Biology - Habel, Jan Christian (Springer-Verlag Berlin Heidelberg, 2010)
This book provides an overview of the importance of research on relict species and presents conclusions and findings on the conservation of these species. There are relict species and populations from nearly all plant and animal groups and they contribute substantially to biodiversity across the globe. Current diversity patterns are influenced by both historic and recent ecological conditions. Relict species are of particular importance, as they usually suffer more severely from human activities than do non-relict populations, the situation is also potentially critical, as many relict species and populations have the potential to colonize large areas when the climate changes. The more than 27 contributions in this book highlight the history and status of today's relict species and populations and apply molecular genetics, morphometry, modelling and conservation biology to describe the past and present situations and to predict future trends of relict species' distribution.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Phylogenie; Populationsbiologie; Seltene Pflanzen; Seltene Tiere